Membangun Platform Digital Desa Margamulya Tanjung Kait Untuk Menuju Masyarakat Society 5.0 - Hayat, Cynthia; marcel, marcel; Putro, Endi; Windarto, Yudhi; Perangin Angin, Prasasti; Mudita, Damida Shu; Setiawan, Theodorous Stevanus; Christian, Juan; Putratama, Andhika; Christian, Neil (STMIK Royal, 2024)
The village of Margamulya Tj. Kait is one of the foster villages of LPPM Ukrida. From the results of interviews and direct observations, there are several main issues faced by partners, including: limited access and dissemination of financial information and village profiles to external parties as well as to the villagers themselves. Community service is conducted by utilizing technology to develop a digital village community ecosystem where social media-based platforms serve as everyday communication, socialization, and collaboration tools. The implementation method is carried out through: (1) development of social media platforms; (2) training on platform usage. With the developed social media platform program, the target output is achieved through the evaluation of activities, where the benefit of interaction between village officials and villagers, as well as the dissemination and access to important information, becomes easier. Keywords: digital platform; village digitalization; digital village; margamulya village